Associations between periodic social events and status epilepticus—An 11‐year cohort study. (25th May 2018) - Hollinger, Alexa; Semmlack, Saskia; De Marchis, Gian Marco; Spiegel, Rainer; Hunziker, Sabina; Rüegg, Stephan; Marsch, Stephan; Sutter, Raoul
Summary: Objectives: Periodic social events may influence the incidence and course of status epilepticus (SE), likely explained by patients' behavioral changes regarding alcohol intake, sleep, and compliance with antiseizure medication. However, data regarding the association between such events and SE are lacking. The aim of this study was to identify and quantify associations between periodic social events and the incidence, etiology, and outcome of SE. Methods: Adult patients who were admitted to a tertiary academic medical care center with SE from 2005 to 2015 were included. Associations between periodic social events (including birthday, Christmas, New Year's Eve, carnival, national holiday) and the number and etiologies of SE over time were calculated using linear and Poisson regression. Logistic regression was applied to identify associations between time from social events and outcome. Results: Four hundred nine patients with a median age of 66 years (interquartile range 52‐76) were analyzed. The number of total SE events and SE in patients with known epilepsy peaked within 2 weeks following social events and then decreased with each additional day (incidence rate ratio [IRR]per day 0.99, 95% confidence interval [CI] 0.98‐0.99; P < .001 and IRRper day 0.99, 95% CI 0.98‐0.99; P < .001, respectively) and week (IRRper week 0.94, 95% CI 0.93‐0.95; P < .001 and IRRper week 0.94, 95% CI 0.92‐0.96; P < .001, respectively). The highest proportion of epilepsy patients not taking antiseizure medication was seen closest to social events and decreased thereafter (IRRper day 0.99, 95% CI 0.98‐0.99; P = .003). There was no association between time from social events and outcome. Significance: Our findings support the hypothesis that periodic social events in adults may be associated with an increase in SE and should heighten awareness for SE in this context. Clinicians are urged to inform epilepsy patients regarding this association and to instruct them on preventive measures around such events.